An investigation of cross-cultural social tagging behaviours between Chinese and Americans. Issue 1 (5th February 2018) - Hu, Qian; Lin, Xin; Han, Shuguang; Li, Lei
Abstract : Purpose: The purpose of this paper is to explore different tagging behaviours between Chinese and Americans by analysing the movie tags, and explore the feasibility of applying cultural differences to tag recommendations. Design/methodology/approach: This paper introduced hypotheses based on several well-established psychological theories and tested them with social tags for the same movies generated by Chinese and Americans. And to prove the utility of the cultural factor consideration, this paper conducted a cross-cultural tag recommendation experiment. Findings: The results show that compared with Americans, Chinese users tend to add more tags about movies' background information (e.g. release year) and global contextual characteristics (e.g. genre); they also prefer to add tags about production countries and factual tags, and cultural factors can be applied for recommending more accurate tags. Research limitations/implications: Other reasons for tagging differences beyond cultural factors have not be explored. Tags for some sample movies in MovieLens might be unstable, as they had been tagged by a small scale of users; as a result, the tags' type distribution might be influenced. Practical implications: The results and conclusion of this study will be beneficial for the cross-cultural applications of social tags and mining users' interests based on tags. Originality/value: This paper provided a deeper investigation of the cross-cultural effect in people's social tagging behaviours from cognitive perspective, and an empirical analysis has been performed to explore proper approaches of incorporating cultural differences for tag recommendation.